Problem Based Video Learning on Civic Education Content for Third Grade of Elementary School - Eka Safitri; I Kadek Suartama; Alexander Hamonangan Simamora (Universitas Pendidikan Ganesha, 2024)
Currently, the civic education learning outcomes of elementary school students are still in the low category. This is due to the lack of learning media that can be used. This development research aims to analyze the design, validity and effectiveness of problem-based learning videos on class III civic education content. This research uses the ADDIE development model. The subjects in this research were subject content experts, design experts, media experts, 3 students for individual trials, and 6 students for small group trials. Data collection was carried out using questionnaires and tests. Data analysis techniques use qualitative data analysis, quantitative descriptive data analysis, and inferential statistical data analysis (t-test). The research results show that the video development design includes the stages of analysis, design, development, implementation and evaluation. The assessment of learning media experts showed a percentage of 82.35%, design experts 90.25%, material experts 81.66%, individual trials 96.20%, and small group trials 90.52%. This learning video is effective for use in class III civic education content, especially material on ethnic diversity. It can be concluded that the problem-based learning video innovation in class III civic education content is in very good qualifications and is effectively used to improve student learning outcomes. This research has implications for improving the quality of civic education learning through quality media.